Optimlisasi Media Pembelajaran Abad 21 Berbasis Merdeka Belajar melalui Program Pengabdian Kepada Masyarakat - Supentri, Supentri; Hambali, Hambali; Hasibuan, Hamdi Abdullah; Harahap, Rizky Dinda Sarmita (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2026)
The challenges of 21st-century education require schools to provide learning processes oriented toward strengthening student competencies, such as critical thinking, creativity, collaboration, and communication. However, in practice, there are still limitations in the use of learning media relevant to student characteristics and the Merdeka Belajar policy, particularly at the junior high school level. This community service activity aims to optimize the use of 21st-century learning media through the Independent Community Service program at SMP Negeri 3 XIII Koto Kampar. The implementation method uses an educative and participatory approach through the stages of observation, mentoring, training, implementation, and evaluation. The results of the activity indicate that optimizing 21st-century learning media can increase active student engagement, create more interactive and contextual learning, and enhance teachers' pedagogical competence in designing innovative learning. This activity contributes to strengthening the implementation of independent learning at the junior high school level. It is recommended that schools integrate the use of 21st-century learning media sustainably as part of their learning culture.